The worldwide molecular spectrum and distribution of thalassaemia: a systematic review - Mina Ebrahimi; Javad Mohammadi-Asl; Fakher Rahim (Taylor & Francis Group, 2021)
Context Thalassaemia is one of the most common inherited autosomal recessive disorders around the world. A considerable amount of literature has been published about the type of mutations and the prevalence of thalassaemia, but findings are often contradictory. Objective This systematic review aimed to provide a comprehensive view of the prevalence of thalassaemia-associated mutations in different countries, their effect on haemoglobin (Hb) levels, as well as reporting thalassaemia-associated rare mutations. Methods A systematic search of the literature was carried out through major indexing databases (MEDLINE/PubMed, Scopus, EMBASE, Cochrane central, and ISI web of science) using keywords: "Co-inheritance, αα, β, thalassaemia" and "α-β thalassaemia, Mediterranean anemia, mutations" from 1998-September 2019. Hand-searching was also performed. There was no language restriction. Results The initial searches yielded 1059 studies, of which 92 articles were included following inclusion and exclusion criteria. Of these, 3.3% (3) of articles were cohort studies, and 96.7% (89) of the remaining articles were cross-sectional studies. Our findings showed that 45.6% (42) of researchers investigated β-thalassaemia, 22.9% (21) αα-β thalassaemia, and 31.5% (29) α thalassaemia. Conclusion The present study provides valuable information about the spectrum of thalassaemia-associated mutations, which can be useful for preventing thalassaemia, reducing costs of care, reducing the treatment-related side effects, and showing the most defective mutations.Highlight Evaluating the increase or decrease in the birth prevalence of thalassaemia Identifying the most common and rare mutations in various parts of the world Comparing researchers' findings from various parts of the world